Preparation and Characterization of Toxic Metal Complexes of Nicotinamide and Nicotinic acid (Journal of Bangladesh Academy of Sciences, 2017)
Cd(II), Hg(II) and Pb(II) were reacted with nicotinamide and nicotinic acid (vitamin B3) in the aqueous medium. The solid products obtained were formulated by comparing the experimental and calculated data for C, H, N and metal. Both produce 2:1 compounds with the metal ions. The prepared complexes were characterized by different physicochemical methods. The UV-vis, FTIR spectral analysis, TG analysis of these complexes have been discussed. The conductance behavior of the complexes indicates that all of them behave as weak electrolytes.Journal of Bangladesh Academy of Sciences, Vol. 41, No. 1, 37-45, 2017